Peptide-Driven Nanotheranostics: Simultaneous Targeting, Imaging, and Therapy of Malignancies - Mamatha H S; Ashok Kumar B.S; Disha N. S (The Bioscan, 2025)
Peptide-guided nanotheranostics is a revolutionary strategy in oncology that combines targeted therapy, imaging, and diagnostics on a single platform to overcome the drawbacks of traditional cancer therapies. Even with the advancement of surgery, chemotherapy, and radiotherapy, the issues of low drug solubility, systemic toxicity, and multidrug resistance remain. Peptide-functionalized nanoparticles (peptide-f-NPs) are a potential solution that takes advantage of the biocompatibility, biodegradability, and tumor-targeting specificity of peptides to improve drug delivery and imaging accuracy. These nanocarriers (liposomes, polymeric nanoparticles, dendrimers, and inorganic NPs) are designed with tumor-penetrating peptides (e.g., RGD, NGR) or receptor-targeting peptides (e.g., DOTATATE, bombesin analogs) to impart active targeting, bypassing the heterogeneity of tumor microenvironments. Sophisticated imaging modalities like fluorescence, MRI, PET/SPECT, and photoacoustic imaging are combined with therapeutic payloads (chemotherapeutics, siRNA, photothermal agents, and radionuclides) for real-time monitoring and precision therapy. But despite challenges of peptide instability, RES-mediated quick clearance, immune response, and production complexity, innovation in peptide engineering (cyclization, PEGylation) and nanocarrier design for multifunctionality seeks to advance stability, diminish toxicity, and increase clinical translatability. This review captures the potential of peptide-based nanotheranostics to revolutionize cancer therapy while meeting present limitations and future prospects for clinical translation.